OPTIMALISASI NILAI AGAMA DAN MORAL ANAK USIA DINI MELALUI KEGIATAN BERCERITA - Titien Ruswanti; Muhammad Turhan Yani; Achmad Sya’dullah (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2024)
This study aims to optimize religious and moral values in early childhood through storytelling. Early childhood represents the next generation that requires character education from an early age. Early Childhood Education (PAUD) plays a crucial role in shaping children's character and morals according to religious values. The storytelling method with Islamic themes was applied in this study to enhance the development of religious and moral values in children at POS PAUD Harapan Bunda, Kampar Kiri Hilir District. The results showed that before the implementation of the storytelling method, the development of children's religious and moral values was categorized as "Not Yet Developed." After applying the storytelling method over two cycles, there was a significant increase: from the initial cycle to cycle I by 28.7%, and from cycle I to cycle II by 51.3%, with an overall increase of 94.81%. The storytelling method proved effective in enhancing religious and moral values, helping children develop strong character and noble morals